PEMIDANAAN TERHADAP PENGEDAR DAN PENGGUNA NARKOBA : Penelitian Asas, Teori, Norma dan Praktik Peradilan - Mulyadi, Lilik (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2012)
Formulation types of criminal sanctions (strafsoort) is considered the most appropriate, appropriate and fair for appropriate drugdealers Narcotics Act (Act No. 35of 2009) and Psychotropic Substances Act (Act No. 22 of 1997) andjudicial practicebe assessedfrom the perspective of the principles, theories, norms andjudicial practiceis a system of cumulative-alternative formulation (mixed /combined) between the death penalty, life imprisonment or imprisonment, or a fine, while the length of the formulation of criminals anctions (straafmaat) is considered the most appropriate, appropriateand fair sentenceis a determinate system in the form prescrib edlimit minimum and maximum criminal threats. Punishment for drug user alyzed from the perspective of the principles, theories, norms and practices of its application to the dealers to berelatively severe punishment metedranging from the death penalty, life imprisonment and criminal casesover the past 15-20 years. The nthenature of drug users a sactors (daders) and a victim (victims) in addition to drug crimeshould bedropped also dropped criminal sentencing rehabilitationas stipulated in Article 127 of LawNo. 35 of 2009 for narcoticaddicts. Keywords: Formulation types of criminal sanctions, formulation of criminals anctions (straafmaat)